Bevacizumab in Neoadjuvant Treatment of Patients with Liver Metastases from Colorectal Carcinoma - Uddin, Dayem; Khan, MMR; Rahman, ASMM; Habib, Shafayat; Sultana, Shakera (TAJ: Journal of Teachers Association, 2018)
Liver metastases are the leading cause of death in patients with colorectal cancer Despite advances in chemotherapy, surgical resection of hepatic metastases is still considered the only curative treatment the majority of patients have inoperable disease at presentation. Perioperative chemotherapy is the most successful way for improved selection of patients for resection. The aim of the study was to demonstrate if and to what extent does bevacizumab, introduced in chemotherapy, increase response rates, and development of liver metastases. Our study included 25 patients who were divided in two groups. The experimental group included patients who were treated with bevacizumab plus chemotherapy and the control group included patients who were treated with chemotherapy only. The comparison showed that the patients who were treated with bevacizumab became candidates for resection of liver metastases in higher percentage (85%:52%). On the otherhand distribution of patients regarding the development of metastases resulted in statistically significant difference. Ratio between the patients with good response from the experimental and the control group was 67%:39%. Ratio of patients with stable disease was 26%:48%, and of patients with progressive disease, it was 7%:3%. The estimate of margin after resection was statistically insignificant. TAJ 2011; 24(2): 101-105